"Who is wise and understanding among you" (James 3: 13)? An analysis of wisdom, eschatology and apocalypticism in the epistle of James - Hartin, Patrick (Hervormde teologiese studies, 1997)
Three questions form the basis of this analysis of the relationship of the Epistle of James to the traditions of wisdom, eschatology and apocalypticism. What kind of traditions are involved in James? What is the world view of James? What audience or community is presupposed by this writing? Foremost is the connection that James demonstrates to the wisdom tradition evident in the Old Testament and extratestamental literature. In particular two types of wisdom tradition are noted in James: practical wisdom advice as expressed in short sayings, wisdom instructions and admonitions and reflection on the nature of wisdom (1:5-8; 2:1-7; and 3:13-18) as coming from God. Finally, the question of how much apocalyptic symbolism is evident in the eschatological world view of the epistle is addressed.